The Effect Training Program In Using Repetitive Training Of Force Explosive Armrests To Enhancethe Boxing Players’ Straight Punch - Aroussi, Abdrazak (sports creativity, 2025)
The study aims to determine the effect of using repetitive training for explosive power of the arms in improving the straight punch of boxers. A field study of the sports club for amateur boxers whose boxers are active in the state and national championships. This is in order to highlight the effect of the proposed training program in improving the performance of boxers during national and international championships. This study aims to improve the straight punch of the boxer, considering it to be one of the most important motor skills of the boxer.